Artificial Intelligence in Public Relations: Potential Benefits and Drawbacks - Ömer Faruk Zararsız (Yeni Medya)
The functioning of institutions and organizations, as well as the lives of individuals, have been significantly impacted by artificial intelligence technologies becoming an essential part of everyday life. One area that has been greatly affected by these technologies is public relations. Within the realm of public relations, artificial intelligence offers numerous advantages in terms of time and cost, particularly in areas such as customer relationship management, media and social media monitoring and analysis, virtual assistants, internal communication, and crisis communication and management. However, the use of artificial intelligence also poses potential threats in areas that are crucial to the success of public relations, such as propaganda, privacy, data breaches, ethics, disinformation, and misinformation. As a result, international organizations, academics, and public relations professionals have put forth various suggestions to prevent the misuse of artificial intelligence in damaging the reputation of institutions, organizations, and the field of public relations as a whole. This study aims to explore the potential advantages, threats, and recommendations associated with the use of artificial intelligence technologies in public relations through a comprehensive literature review.